Impact of the financial crisis on revenues of urban municipalities in Poland – experiences the COVID-19 pandemic - Maj-Serwatka, Katarzyna; Wichowska, Anna (Rozwój Regionalny i Polityka Regionalna, 2024)
The COVID-19 pandemic has given rise to grave economic consequences, especially for the public finance sector, both at the central and local government level. The aftermath of the pandemic-induced crisis began to be felt particularly by local government units (LGUs), which are responsible for the implementation of most public tasks at local level. As a consequence, the role of budget planning increases and the rationalization of public expenditure in response to declining revenues becomes important. This paper is in line with the ongoing discussion on the implications of the COVID-19-induced crisis. Two research goals were formulated. The former was to assess the effects of the crisis caused by the COVID-19 pandemic on budget revenues and indirectly on the financial standing of Polish urban municipalities, and the latter was to identify changes in the structure of urban municipalities budgets in Poland as a consequence of the pandemic. For the needs of the study, we used an indicator analysis of urban municipalities budgets, which allows for a synthetic determination of the financial condition and verification of development decisions. The aim of the research was achieved by analyzing the dynamics of indicators that characterize urban municipalities budget revenue in Poland. The scope of research covered the years 2010–2022. The results and the formulated practical recommendations constitute a complementation of the research on the effects of the COVID-19 pandemic for public finance, in particular the finances of local government units. The analyses demonstrate a shift in the urban municipalities revenue structure in Poland, which is the effect of a decreased share of own revenue, especially tax revenue, and an increase in the share of transfer revenue. This was due to three factors. Two of them were directly related to the COVID-19 pandemic, i.e 1) reduction in tax revenue (mainly from shares in PIT) as a result of the lockdown and the economic crisis; 2) options of support for local governments in the form of increasing transfer revenue. The third factor that contributed to the decline in own revenue are changes unrelated to the pandemic. These include, for example, changes in personal income tax or changes in the “Family 500+” programme.